3D plotting of growth factor loaded calcium phosphate cement scaffolds. (November 2015) - Akkineni, Ashwini Rahul; Luo, Yongxiang; Schumacher, Matthias; Nies, Berthold; Lode, Anja; Gelinsky, Michael
Graphical abstract: Abstract: Additive manufacturing allows to widely control the geometrical features of implants. Recently, we described the fabrication of calcium phosphate cement (CPC) scaffolds by 3D plotting of a storable CPC paste based on water-immiscible carrier liquid. Plotting and hardening is conducted under mild conditions allowing the (precise and local) integration of biological components. In this study, we have developed a procedure for efficient loading of growth factors in the CPC scaffolds during plotting and demonstrated the feasibility of this approach. Bovine serum albumin (BSA) or vascular endothelial growth factor (VEGF), used as model proteins, were encapsulated in chitosan/dextran sulphate microparticles which could be easily mixed into the CPC paste in freeze-dried state. In order to prevent leaching of the proteins during cement setting, usually carried out by immersion in aqueous solutions, the plotted scaffolds were aged in water-saturated atmosphere (humidity). Setting in humidity avoided early loss of loaded proteins but provided sufficient amount of water to allow cement setting, as indicated by XRD analysis and mechanical testing in comparison to scaffolds set in water. Moreover, humidity-set scaffolds were characterised by altered, even improved properties: no swelling or crack formation was observed and accordingly, surface topography, total porosity and compressive modulus of the humidity-set scaffolds differed from those of the water-set counterparts. Direct cultivation of mesenchymal stem cells on the humidity-set scaffolds over 21 days revealed their cytocompatibility. Maintenance of the bioactivity of VEGF during the fabrication procedure was proven in indirect and direct culture experiments with endothelial cells. Statement of Significance: Additive manufacturing techniques allow the fabrication of implants with defined architecture (inner pore structure and outer shape). Especially printing technologies conducted under mild conditions allow additionally the (spatially controlled) integration of biological components such as drugs or growth factors. That enables the generation of individualized implants which can better meet the requirements of a patient and of tissue engineering constructs. To our knowledge, simultaneous printing of biological components was up to now only described for hydrogel/biopolymer-based materials which suffer from poor mechanical properties. In contrast, we have developed a procedure (based on 3D plotting of a calcium phosphate cement paste) for the fabrication of designed and growth factor loaded calcium-phosphate-based scaffolds applicable for bone regeneration.